Crisis-proof households? How social policy responses to the COVID-19 pandemic imagined work and care in Germany - Hannah Zagel; Emanuela Struffolino (Journal of Social Policy, 2024)
Social policies convey normative assumptions about how households should make ends meet and organise care, but how do these ideals withstand crises such as the coronavirus disease 2019 (COVID-19) pandemic? Previous research shows continuity of welfare state models in the crisis, but mostly looked at single policy fields and produced mixed findings regarding the role of pre-crisis reform trajectories. This paper contributes a detailed analysis of assumptions about the `standard productive household' in terms of three dimensions: labour market participation, coverage of economic needs and coverage of care needs. Drawing on original policy documents enacted in 2020 in Germany – which had dismantled many of its institutional strongholds for the male-breadwinner model before the crisis – we provide two novel insights. First, social policy responses to the pandemic were relatively coherent regarding assumptions about labour market participation, but expectations towards households' abilities to make ends meet and parents' care involvement were less coherent. In addition to relaxing conditions on stable employment and income, policy responses normalised patchwork incomes and relied on parents to compress paid and unpaid work. Second, we propose that crises may slow down reform processes that are already underway by reverting to ideas that were dominant in the past.
Keywords: 320; COVID-19 pandemic; social policy responses; ideal-type household; Germany